Elaboración de ha M burguesa de P aco (Piaractus brachy P omus ) usando soya texturizada y aceite de sacha inchi (Plukenetia volubilis) - pinedo F y Cols., Jhenny Isabel (2019)
This work was developed at the universidad nacional agraria de la selva. The objective was to determine the formulation of fish burgers with textured soy and sacha inchi oil, and evaluate the cooking time of the burgers and its progress during storage. The raw material was paco fish obtained from the instituto amazonía (iiaP). to determine the formulation of hamburgers, treatments varied in textured soy: sacha inchi oil, and were: t1 (0%:5%), t2 (0%:7.5%), t3 (0%:10%), t4 (2.5%:5%), t5 (2.5%:7.5%), t6 (2.5%:10%), t7 (5%:5%), t8 (5%:7.5%) and t9 (5%:10%), this was determined by sensory testing of balanced incomplete block design, incomplete and complete block test, and the “t” test. to determine the burger cooking time it was subjected to 85 °c for 5,10 and 15 minutes, and it was evaluated by the crac. The progress during storage was evaluated by the ph, humidity, tbars, sensory and microbiological evaluation. The nine treatments were evaluated by three balanced incomplete block design treatments t6, t5 and t7 for the attributes of texture, flavor and general appearance, where it was determined that t5 was the better treatment. The cooking time for hamburgers was 5min/85 °c, with a 16.113% crac. During storage for 20 days burgers showed good physicochemical and microbiological characteristics.